Development of a Scale to Measure Religiosity Anxiety in Puerto Rico - Álvarez-Alatorre, Yazmín (Journal of psychology and theology, 2024)
This research aimed to develop an instrument to measure symptoms of religious anxiety considering its physical, behavioral, and cognitive manifestations, according to the DSM-5-TR. The final sample consisted of 302 adult residents of Puerto Rico with ages ranging from 21 to 73 years (M = 42.74, SD = 12.80). Exploratory factor analysis, internal consistency analysis, and correlation analysis with other anxiety scales and spiritual struggles were performed. The factor analysis identified a two-dimensional structure: physical and cognitive manifestations of religiosity anxiety. The internal consistency of the scale was adequate (α = .95; ω = .95). It is concluded that the Religiosity Anxiety Scale has sufficient evidence of validity, and we propose it as a practical and helpful tool in Puerto Rican clinical and academic work. The practical implications and limitations of the findings are discussed.